Microsurgery of Cerebral Aneurysm: Epidemiological Profile - Ribeiro, Luiz Roberto Tomasi; De Menezes, Rubens Thadeu Mangilli; Madeira, Kristian; Moreira, Carlos Fernando dos Santos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Objectives Intracranial aneurysm consists of localized dilatation of the vascular wall. Its importance includes the fearsome event of rupture and subarachnoid hemorrhage, which presents high morbimortality rates. The present study aimed to analyze the profile and clinical outcome of patients submitted to the microsurgical approach of cerebral aneurysm in the city of Criciúma, state of Santa Catarina, Brazil, from 2015 to 2018.Methods A retrospective observational study was performed, with secondary data collection and a quantitative approach of 47 charts.Results A predominance of females (74.5%) and a mean age of 53 years old (53.53 ± 9.64) was observed. The middle cerebral artery was the most affected vessel (36.2%), with the highest percentage of aneurysms being between 2.1 mm and 7.0 mm (65.9%). There was a correlation between consciousness level and classification on the Hunt-Hess (HH) scale. Patients with Glasgow Coma Scale (GCS) > 7 points had a better prognostic score in the HH scale, and those with GCS ≤ 7 points had a worse prognostic score in the HH scale.Conclusions The present study observed the presence of important risk factors for cerebral aneurysm formation, such as gender, age, smoking, and systemic arterial hypertension. The present study can measure a correlation of the level of consciousness with the HH classification.
Keywords: intracranial aneurysm; microsurgery; subarachnoid hemorrhage